Using Raman spectroscopy and structural properties in understanding the ferroelectric nature of the RbMgPO4 phase transitions. (July 2021) - Gharbi, I.; Oueslati, A.; Bulou, A.; Gargouri, M.
Graphical abstract: Highlights: EDS/SEM analysis proved the purity of the RbMgPO4 compound with a uniform grain distribution with a microrod-like structure.. DSC analysis reviled the existence of two reversible phase transitions located at T1 and T2 . T1 discloses the coexistence of order-disorder and displacive components, while T2 appears as a displacive one. The Raman analysis showed that external modes are the most influenced by temperature. The number of correlated unit cells decreases and the structure becomes more disordered at high temperatures. Abstract: Rubidium magnesium monophosphate RbMgPO4 compound was synthesized using the solid− state method. XRPD analysis, at room temperature, confirmed that the sample exhibits an unusual three-fold Pna21 superstructure in the orthorhombic system. EDS analysis proved the absence of external elements. SEM micrograph showed a microrod-like structure of grains with a uniform distribution. This compound undergoes two phase transitions of a ferroelectric nature at T1 = 448/433 K and T2 = 466/458 K (Heating/Cooling) revealing a rich polymorphism in the solid-state. These phase transitions were investigated using Raman spectroscopy analysis. The first shows a moderate reconstructive character revealing the coexistence of order-disorder and displacive components, while the second appears as a displacive one. These transitions are originated from the rotation of both MgO4 and PO4 in an inverse direction and a change of Mg coordination, to reach a high symmetry. Based on the order-disorder model, the analysis of the wavenumber, intensity, and width allowed us to attain information and to determine the thermal coefficients and the activation energies in each region. The temperature dependence of Raman spectra showed that the most important changes were observed in the external modes. The estimated critical values of the exponents (δ1, δ2 ) and (ξ01, ξ02 ), deduced from the reduced intensity of the thermosensitive band, were determined.